Evaluasi Program Pendidikan Guru Penggerak di Kabupaten Lombok Utara NTB - Rohman, Moch. Fatkoer; Sudirman, Sudirman; Waluyo, Untung; Sumardi, Lalu; Fahruddin, Fahruddin (Jurnal Paedagogy, 2023)
This research aims to evaluate the impact of guru penggerak (mobilizer teacher) education program in Lombok Utara Regency, West Nusa Tenggara. The research method used was quantitative descriptive with the Kirkpatrick evaluation research model. The criteria for the impact of the mobilizing teacher education program consist of 1) the impact on the development of oneself, others, and the school; 2) the impact on learning in favor of students. The locations of this research were SDN 8 Sokong, SMPN 3 Tanjung, SMAN 1 Tanjung, and SMKN 1 Gangga, with a purposive sampling technique totaling 20 people. Data was collected using questionnaires and interviews and then analyzed using the PEA (Percentage of Each Aspect) formula. This study found that the impact of the mobilizer teacher education program on the development of oneself, others, and schools was good, with a final score of 86.4%. The impact of the mobilizer teacher education program on impactful learning on students was excellent, with a final grade of 93.2%. Thus, the impact of the North Lombok mobilizer teacher education program in North Lombok Regency, West Nusa Tenggara is good, with a final score of 89.9%.